MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE DISKUSI KELOMPOK NHT ( NUMBERED HEADS TOGETHER ) DALAM PROSES PEMBELAJARAN SOSIOLOGI DI SMAN 16 PADANG - Sainur, Veby Maigem (Pendidikan Sosiologi, 2014)
This study originated from the fact that the average student XII IPS subjects in Highschool sociology course 16 Padang is still much below the, One way to overcome this is byapplying a model of NHT. This study uses an experimental approach to study the differencesin the results of the sociological study of NHT model with the conventional model. The studypopulation was all students of class XII 1PS SMA 16 Padang Courses listed in the academicyear 2013/2014 and techniques in sampling is purposive sampling so that the sample is aclass XII IPS 3 as the experimental class and XII IPS 4 as the control class. Collecting data inthis study using the test results of a study about the objectives of 20 items. Data wereanalyzed using two average difference (t test).From the research that the implementation ofthe use of the model of NHT on the subjects of Sociology provides better results compared tothe results of a study that uses only conventional models. It can be seen from the averagestudent experiment class 78.25, while the control group 69.5. Based on statisticalcalculations, it can be t have a larger value compared with the t t = 2.63> t = 2.000 at 0.05level of significance, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha)is accepted, then the difference significant student learning outcomes using NHT model withthe conventional model on subjects Sosilogi class XII IPS SMA 16 Padang.